2018
DOI: 10.1177/0194599818770413
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Sporadic Vestibular Schwannoma: A Volumetric Study of Tumor Growth

Abstract: Objective (1) Assess 3-dimensional volumetric growth of untreated sporadic vestibular schwannomas (VSs) in a large cohort of patients treated with conservative observation. (2) Compare volumetric and conventional linear diameter measurements for detecting tumor growth. Study Design Case series with chart review. Setting Tertiary skull base referral center. Subjects and Methods Patients with sporadic VS who elected initial conservative treatment with at least 2 serial magnetic resonance imaging (MRI) scans were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
127
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(137 citation statements)
references
References 21 publications
8
127
1
1
Order By: Relevance
“…The risk of growth after 5 years of follow-up ranges from 0 3 to 7%, 8 with some recent studies having demonstrated tumor growth after many years of follow-up. [9][10][11][12] These studies recommend continuing a lifelong policy of surveillance imaging, albeit at a reduced interval frequency for stable tumors. However, these papers have not specifically focused on the older patient age group, and our data suggest that a policy of discontinuation of imaging surveillance after 5 years tumor stability can be considered in this group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of growth after 5 years of follow-up ranges from 0 3 to 7%, 8 with some recent studies having demonstrated tumor growth after many years of follow-up. [9][10][11][12] These studies recommend continuing a lifelong policy of surveillance imaging, albeit at a reduced interval frequency for stable tumors. However, these papers have not specifically focused on the older patient age group, and our data suggest that a policy of discontinuation of imaging surveillance after 5 years tumor stability can be considered in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is possible that some of these tumors (such as tumors in younger age groups) may also grow with time, given longer follow-up or a larger cohort, as has been shown in other nonage-segregated studies. 11,12 We also do not have data at 10 or 20 years, and therefore cannot say with certainty that the risk of growth later is zero but only that it is likely to be low. To change recommendations in the elderly requires either a documented change in the biological behavior of tumors in older adults or a change in the utility of treatment when balancing risks and rewards of treatment versus nontreatment.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent large retrospective study, while 48% of observed tumors had linear progression over 1.8 years and 69% demonstrated volumetric growth over 1.1 years. 4 In another cohort with longer follow-up, only 37% of tumors limited to the internal auditory canal demonstrated linear growth progression after nearly 10 years of observation. 5 Further, tumor growth does not necessarily mandate treatment.…”
Section: Introductionmentioning
confidence: 91%
“…For this reason, many patients are told of a typical slow growth pattern or that their tumor "may not grow at all." Two recent studies (from the Mayo Clinic 23 and NYU [unpublished data]) used serial volumetric measurements and high-resolution imaging techniques to define tumor growth patterns. The Mayo study showed that 69% of patients had volumetric growth within a median of 1.1 years.…”
Section: Vestibular Schwannomasmentioning
confidence: 99%
“…The Mayo study showed that 69% of patients had volumetric growth within a median of 1.1 years. 23 The NYU study showed that over an average 2-year follow-up interval, approximately 30% of patients did not have significant tumor growth (< 20% by volume) and that in 70% of cases the tumor did grow by more than 20%, with half of those tumors growing by more than 100% per year. Thus there are both slower and faster growth groups.…”
Section: Vestibular Schwannomasmentioning
confidence: 99%